The auditory function in migraine model rats induced by postauricular nitroglycerin injection - Qi, Rongxiang; Zhang, Jilei; Diao, Tongxiang; Yu, Lisheng (Frontiers in Neurology, 2023)
Objective The mechanism by which migraines produce inner ear-related symptoms is not well understood. Previous studies have found that the latency of auditory brainstem response (ABR) in animal models of migraine has changed, but the threshold has not changed significantly. Therefore, it is necessary to establish a better animal model with both migraine and hearing loss to explore the relationship between migraine and auditory function deeply. Methods In this study, the rat model of migraine was induced by postauricular injection of nitroglycerin (NTG), and the effect on the auditory function of the inner ear was explored by comparing with intraperitoneal injection of nitroglycerin. The rats were given the drug repeatedly on alternate days, a total of 5 dosing, with the body weight monitored during the drug administration. The tactile threshold of the rats' forepaw was measured using von-Frey filaments and auditory function was assessed by ABR. Results The results showed that the baseline tactile threshold of rats gradually decreased during the modeling process, and hyperalgesia appeared. Postauricular injection of NTG did not affect the weight gain of rats, while intraperitoneal injection of NTG showed slow or even negative weight gain. The ABR threshold of Click, 4 and 8 kHz of postauricular NTG injection rats increased, the latency was prolonged, and the ABR threshold in the right ear was higher than that in the left ear. Conclusions We demonstrated that postauricular injection of nitroglycerin may be safer and more effective than intraperitoneal injection of nitroglycerin in the process of creating rat migraine model without affecting the weight gain. Postauricular injection of nitroglycerin has more damage to the auditory function of rats. Therefore, the migraine model rat induced by postauricular injection of nitroglycerin may be a new model of cochlear migraine.